Rural Status, Suicide Ideation, and Telemental Health: Risk Assessment in a Clinical Sample. Issue 2 (25th June 2018) - Tarlow, Kevin R.; Johnson, Tina A.; McCord, Carly E.
Abstract: Objective: Individuals living in rural areas die by suicide at higher rates than those living in metropolitan areas. Telemental health interventions provide rural residing individuals with access to needed care. Identifying telemental health clients at risk for suicide is an important task for clinicians and policymakers. This study evaluated to what degree rural status and other demographic variables predicted suicide ideation in clients seeking services at a telemental health clinic. Methods: Study participants included 457 low‐income clients residing in the medically underserved, geographically diverse Brazos Valley region of Texas. Clients completed the patient health questionnaire during their initial counseling appointment, which assessed depression severity and suicide ideation in the 2 weeks prior to assessment. Results: Suicide ideation was common among telemental health clients, with approximately 40% of clients in all demographic groups reporting some recent thoughts of suicide. Rates of suicide ideation did not significantly differ by geographic designation (ie, rural/metropolitan status), gender, or race/ethnicity. However, depression was a strong predictor of recent suicide ideation. Conclusions: Telemental health programs can effectively connect clinicians with rural residing clients who are otherwise isolated from health care services. However, clinicians working in high‐need, historically underserved areas should be prepared to encounter a high prevalence of suicide ideation and depression. In these regions, clinical and diagnostic features may be better indicators of suicide ideation than demographic variables.